La3Si6N11 - Yamane, Hisanori; Nagura, Toshiki; Miyazaki, Tomohiro (Acta crystallographica. Section E, Structure reports online, 2014)
Colorless transparent single crystals of trilanthanum hexa-silicon undeca-nitro-gen, La3Si6N11, were prepared at 0.85 MPa of N2 and 2273 K. The title compound is isotypic with Sm3Si6N11. Silicon-centered nitro-gen tetra-hedra form a three-dimensional network structure by sharing their corners. Layers of one type of SiN4 tetra-hedra and slabs composed of the two different La(3+) cations and the other type of SiN4 tetra-hedra are alternately stacked along the c axis of the tetra-gonal unit cell. The site symmetries of the two La(3+) cations are are ..m and 4.., respectively.